Policy Formulation and Implementation on Participatory Budgeting in Seoul, South Korea - Suk Kyung Lee (Policy & Governance Review, 2017)
This research analyzes the policy formulation and implementation of participatory budgeting in Seoul by using qualitative methods focusing on document research. The target time for this research is from 2010 until May 2012 when the Seoul government enacted the PB regulation for policy formulation, and from 2012 until 2016 for policy implementation. The results of the research show that Seoul government had already faced many demands for the implementation of PB before the regulation on PB was enacted. These demands are the result of two flows, that is, a political flow that regards citizen participation in the process of public policy as important and the worsening financial condition of the local government. In this situation, the change of Seoul mayor in 2011 has led the Seoul government to start policy formulation for PB. In the process of making the regulations, the CSOs that already studied a lot about PB also participated in this process. So, Seoul government has made regulation on PB with high level of citizen participation. After regulation on PB was enacted, during the implementation of PB, Seoul government seeks to increase the level of citizen participation by enhancing its representativeness and expertise. For example, Seoul government randomly select most of the PB committee members through open recruitment for representatives, make compulsory lessons in budgets school for expertise, and disclose all information and provide more opportunities for participation such as e-voting to increase the number of participants. As a result, the number of e-voting participants reached about 1% among the total population of Seoul.